Intense oceanic uptake of oxygen during 2014–2015 winter convection in the Labrador Sea. Issue 15 (5th August 2017) - Koelling, Jannes; Wallace, Douglas W. R.; Send, Uwe; Karstensen, Johannes
Abstract: Measurements of near‐surface oxygen (O2 ) concentrations and mixed layer depth from the K1 mooring in the central Labrador Sea are used to calculate the change in column‐integrated (0–1700 m) O2 content over the deep convection winter 2014/2015. During the mixed layer deepening period, November 2014 to April 2015, the oxygen content increased by 24.3 ± 3.4 mol m −2, 40% higher than previous results from winters with weaker convection. By estimating the contribution of respiration and lateral transport on the oxygen budget, the cumulative air‐sea gas exchange is derived. The O2 uptake of 29.1 ± 3.8 mol m −2, driven by persistent undersaturation (≥5%) and strong atmospheric forcing, is substantially higher than predicted by standard (nonbubble) gas exchange parameterizations, whereas most bubble‐resolving parameterizations predict higher uptake, comparable to our results. Generally large but varying mixed layer depths and strong heat and momentum fluxes make the Labrador Sea an ideal test bed for process studies aimed at improving gas exchange parameterizations. Key Points: Substantial uptake of oxygen is observed in the Labrador Sea during the 2014–2015 winter Stronger oxygen sink compared to previous studies is linked to North Atlantic Oscillation Many commonly used gas exchange parameterizations underestimate the observed flux dramatically